Photocatalytic activity of CdS and Ag(2)S quantum dots deposited on poly(amidoamine) functionalized carbon nanotubes - Neelgund, Gururaj M. (2011)
Two novel ternary nanocatalysts, f-MWCNTs-CdS and f-MWCNTs-Ag(2)S were successfully constructed by covalent grafting of fourth generation (G4) hyperbranched, crosslinked poly(amidoamine) (PAMAM) to carboxylated multi-walled carbon nanotubes (MWCNTs-COOH) and subsequent deposition of CdS or Ag(2)S quantum dots (QDs). The structural transformation, surface potential, and morphology of functionalized MWCNTs (f-MWCNTs) and nanocatalysts were characterized by UV-vis spectrophotometer, Fourier transform infrared spectroscopy, powder X-ray diffraction, Raman spectroscopy, thermogravimetric analysis, scanning electron microscopy and energy dispersive spectroscopy. Transmission electron microscopy reveals the effective anchoring of QDs on f-MWCNTs. The catalytic activity of nanocatalysts was evaluated by photodegradation of methyl orange under illumination of UV light. The coupling of MWCNTs, PAMAM and CdS or Ag(2)S QDs significantly enhanced the catalytic efficiency of nanocatalysts. The rate constants for degradation of methyl orange in presence of nanocatalysts were calculated using the Langmuir-Hinshelwood model. Overall, the excellence in photodegradation was accomplished by hybridizing f-MWCNTs with CdS or Ag(2)S